Professionally focused vlog in pre-service foreign language teacher education - A. Melnyk (Викладання мов у вищих навчальних закладах освіти на сучасному етапі: Міжпредметні зв'язки)
The phenomenon of “vlogging” is articulated through its pivotal role in the professionally focused communicative competence development of pre-service foreign language teachers, particularly those specializing in English. The exploration encompasses a review of both domestic and international scholarly contributions. A professionally focused vlog is conceptualized as an information and research project that is educational in form and professional in content delineating the trajectory of the prospective teacher’s future career. Its genesis is ascribed to contemporary pedagogical demands for the establishment of an enriching multimedia educational environment, envisioned to foster the augmentation of interaction; the integration of authentic online resources and tasks, inciting students to explore diverse professional and pedagogical issues; the cultivation of the skills pertinent to both independent and collaborative information gathering, transforming it into a profound learning experience that steers clear of a linear sequence in favor of a comprehensive array of sources for forging personalized learning pathways.